Transformation of the Yogyakarta Panji mask style and its relevance in gender identity reconstruction - Slamet Subiyantoro; Yasin Surya Wijaya; Mulyanto Mulyanto (Gelar: Jurnal Seni Budaya, 2025)
This study explores the transformation of the form, function, and meaning of the Yogyakarta Panji mask style and its relevance to gender identity reconstruction. The research employs a qualitative single-case study strategy. Data were collected through in-depth interviews, participatory observation, and content analysis of informants, settings, events, and archival documents. Data validity was ensured through source triangulation and informant review, while analysis followed a flow model consisting of data reduction, data display, and conclusion drawing. The findings show that the Panji mask has undergone transformations in three concrete dimensions. Visually, it has shifted from classical pakem conventions to contemporary designs influenced by wood-batik and tourism aesthetics. Functionally, it has changed from a sacred ritual object into a commodity within the creative economy and cultural tourism. Symbolically, its meaning has expanded from traditional Javanese moral-philosophical values to more contextual interpretations linked to social identity and cultural promotion. These shifts contribute to gender identity reconstruction by enabling more inclusive representations of masculinity and femininity. The evolving visual forms, broader social roles, including the increasing involvement of women in mask making and renewed interpretations of Panji and Sekartaji, demonstrate how traditional arts can promote more egalitarian gender narratives today.